UHPLC-MS/MS-based central carbon metabolism unveils the biomarkers related to colon cancer: Biomarkers of carbon metabolism in relation to colon cancer - Yuan, Weisi; Chen, Yinxing; Zhuang, Dan; Zeng, Hong; Lin, Xihua; Hong, Sigeng; Lin, Fang; Chen, Xiuna; Huang, Shucan; Lin, Fen (Cellular and Molecular Biology, 2023)
Even though colon cancer ranks among the leading causes of cancer mortality, early detection dramatically increases survival rates. Many studies have been conducted to determine whether altered metabolite levels may serve as a potential biomarker of cancer that affects key metabolic pathways. The goal of the study was to detect metabolic biomarkers in patients with colon cancer using liquid chromatography-mass spectrometry (LC-MS). This study consisted of 30 patients with colon cancer. An analysis of the metabolomes of cancer samples and para-carcinoma tissues was conducted. We identified a series of important metabolic changes in colon cancer by analyzing metabolites in cancerous tissues compared to their normal counterparts. They are mainly involved in the pentose phosphate pathway, the TCA cycle, glycolysis, galactose metabolism, and butanoate metabolism. As well, we observed dysregulation of AMP, dTMP, fructose, and D-glucose in colon cancer. Additionally, the AUCs for AMP, dTMP, fructose, and D-glucose were greater than 0.7 for the diagnosis of colon cancer. In conclusion, AMP, dTMP, fructose, and D-glucose showed excellent diagnostic performance and could serve as novel disease biomarkers for colon cancer diagnosis.